Criteria for aquatic planting design in ecological redevelopment of urban riverfronts - Zhu, Jiaying (Kansas State University, 2012)
Urban environmental pollution continues to be exacerbated by a number of factors relating to human population growth including sewage discharged directly into the urban rivers designed with concrete-sealed riverfronts. This has left a number of rivers with deteriorated water quality. Where a riverfront could be the highlight and magnet of the city, it may instead become a stain and waste place. In 1969 American landscape planner McHarg proposed the landscape planning theory, “Design with Nature." His primary argument was that natural processes provide self-regulatory functions that need to be reflected in our plans and designs. Ecological design aims include restoring or promoting natural processes and automatic (bio-physical, regenerative, and adaptive) stabilizers. A wide range of scientific knowledge is available to help guide the designer, but designers usually have limited time to complete their designs. Unfortunately, much of this information is diffusely dispersed in research literature and not easily collected and synthesized by the design community. The purpose of this review is to help provide a synthesis of current thought and to help establish the basis for principles that can aid the designer, offering easy-to-understand design guidelines related to the use of aquatic plants in ecological redevelopment along urban riverfronts. This report focuses on using aquatic plants as the main material to help solve two key problems along riverfront developments: water pollution and flooding. As such this report can serve as a guide for the designer helping them to select aquatic plants using an ecological design approach for the redevelopment of urban riverfronts. It also addresses the essential need to adapt designs based on local site problems and requirements. Since this report provides a review and a basis for where to start in designing with aquatic plants in ecological redevelopment of urban waterfronts, it should not be considered as an exclusive source for the designer but rather a complement to local guidelines and information to derive design solutions.
Keywords: Aquatic plants; Urban riverfront design; Design (0389); Environmental Studies (0477); Horticulture (0471); Landscape Architecture (0390); Land Use Planning (0536)